2016
DOI: 10.1017/s1041610216001022
|View full text |Cite
|
Sign up to set email alerts
|

Can a short internet training program improve social isolation and self-esteem in older adults with psychiatric conditions?

Abstract: The purpose of this study was to investigate whether an educational training course on using the internet and touchscreen technology (TT) would decrease social isolation and improve self-esteem in residents living in a low-level residential facility. Twelve sessions over six weeks with two facilitators were provided to five participants with a variety of psychiatric disorders. Measures were completed before and after the 12 sessions. There were no statistically significant improvements or worsening in social i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Our findings are similar to a previous study that found no difference in social isolation or self-esteem in older adults with psychiatric conditions who took part in twice-weekly internet and technology training over the course of 6 weeks [23]. These participants also reported high satisfaction with the program, and the investigators suggested that a longer training program would be needed to see meaningful improvements.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are similar to a previous study that found no difference in social isolation or self-esteem in older adults with psychiatric conditions who took part in twice-weekly internet and technology training over the course of 6 weeks [23]. These participants also reported high satisfaction with the program, and the investigators suggested that a longer training program would be needed to see meaningful improvements.…”
Section: Discussionsupporting
confidence: 88%
“…Anzai et al (2002) examined an RCT on an training program for illness management skills based on Liberman's community re-entry module, resulting in positive effects including knowledge and skills and community participation. In a small, pre-post study on a short educational training course on using the internet and touch screen, no effects were found on social isolation, self-esteem and internet use (Loi et al 2016). Three studies (Park and Han 2018;Seo et al 2007;Tsang and Pearson 2001) examined societal recovery explicitly focussed on social skills.…”
Section: Societal Recoverymentioning
confidence: 99%
“…Table 1 presents an overview of the structure and delivery features of the 27 programs. A total of 10 programs were for older adults residing in long-term residential care [52] (including nursing home [53][54][55], retirement homes [56], aged care facilities [57], assisted living retirement facilities [58], social housing [59], care homes [60], and veterans' care facility [61]), 16 programs for community-dwelling older adults [62][63][64][65][66][67][68][69][70][71][72][73][74][75], and 2 programs included both community-dwelling older adults and older adults residing in long-term residential care facilities [48,76]. Only 1 program (StoryBox) was designed for exclusive digital intergenerational interactions [70].…”
Section: Structure and Delivery Featuresmentioning
confidence: 99%